Factors Influencing the Morphology of Sea Ice - Matlakala, Boitumelo (Department of Chemical Engineering, 2023)
Due to the continuous melting of sea ice and rising sea levels, more studies are conducted on sea ice morphology and factors influencing the growth of ice. Sea ice is an integral part of the global climate system. It plays a vital role in the polar ecosystem, providing a habitat for organisms. Sea ice growth and behaviour has been observed to be largely affected by climate change and global warming. However, the consequences thereof, on sea ice extent and seasonal changes are still being studied. Artificial sea ice experiments have been used as they offer an advantage of control and help isolate variables during sea ice growth. Additionally, in-situ experiments are expensive, and can present logistical difficulty for measuring these variables long term. Factors such as growth dynamics, crystal texture and brine inclusions were investigated by variation of ambient temperature, starting artificial ocean salinity, reactor volume and the presence of microorganism' secretions: extracellular polymeric substances (EPS). Salinities of 10 psu, 20 psu, and 30 psu, were used at the following temperatures: -20°C, -10°C and -5°C. The temperature and salinity data showed that the growth rate of ice, increases with the decreasing ambient temperature, decreasing starting artificial sea ice salinity, decreasing reactor volume, as well as in the presence of microorganisms' secretions. The cross-polarisation results revealed a decreasing percentage of granular texture with increasing starting artificial ocean salinity and increasing ambient temperature. Similarly, the same trend was observed for increasing reactor volume. In the presence of microorganisms, however, a blotchy granular and a disordered columnar texture were observed. An increase in artificial sea ice porosity due to brine inclusions was revealed by the micro-ct scanning data for an increasing starting artificial ocean salinity. Furthermore, overall porosity increased with decreasing ambient temperature and in the presence of microorganism secretion.